Reactive oxygen species (ROS) generation by lymphocytes in rats treated with a common food additive E407a - Anton Tkachenko (National Scientific Medical Center, 2020)
This research deals with the evaluation of reactive oxygen species (ROS) generation in lymphocytes of rats orally exposed to a thickener and emulsifier E407a (semi-refined carrageenan). There is some evidence that E407a may be toxic and can induce intestinal inflammation. ROS generation in lymphocytes was assessed by flow cytometry using a dye 2',7'-dichlorodihydrofluorescein diacetate (H2DCFDA) in 8 rats treated with 140 mg of semi-refined carrageenan per kg of weight daily during two weeks and 8 control animals. A higher number of ROShigh viable lymphocytes were found in the group of animals exposed to E407a compared with controls. In addition, mean fluorescence intensity (MFI) in ROShigh lymphocytes was elevated, which is indicative of the intensification of ROS production by lymphocytes in response to E407a oral consumption.